Where do we stand in the theory of finance? A selective overview with reference to Erich Gutenberg - Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
For the past 20 years, financial markets research has concerned itself with issues related to the evaluation and management of financial securities in efficient capital markets and with issues of management control in incomplete markets. The following selective overview focuses on key aspects of the theory and empirical experience of management control under conditions of asymmetric information. The objective is examine the validity of the recently advanced hypothesis on the myths of corporate control. The present overview is based on Gutenberg's position that there exists a discrete corporate interest, as distinct from and separate from the interests of the shareholders or other stakeholders. In the third volume of Grundlagen der BWL: Die Finanzen, published in 1969, this position of Gutenberg's is coupled with an appeal for a so-called financial equilibrium to be maintained. Not until recently have models grounded in capital market theory been developed which also allow for a firm's management to exercise autonomy vis-à-vis its stakeholder.
urn:nbn:de:hebis:30-9481
Keywords: B21; G3; L2; 330; corporate finance; corporate control; Erich Gutenberg; internal financing